Valorization of pea pod, celery root peel, and mixed-vegetable peel as a feedstock for biocellulose production from Komagataeibacter hansenii DSM 5602 - KAZAN, DİLEK; GÜNDÜZ, OĞUZHAN; PİNAR, ORKUN (SPRINGER HEIDELBERG, 2022)
Currently, recycling and reuse of wastes to obtain high value-added products are substantial issues for development of sustainable and economic processes. Among these wastes, evaluation of food waste has been received significant attention due to scarcity in undeveloped countries, food security, and environmental problems. In general, this study focused on the investigation of cheap carbon sources and re-utilization of food waste for the production of bacterial cellulose (BC). Therefore, pea pod, celery root peel, and mixed-vegetable peel were evaluated to produce BC from Komagataeibacter hansenii (waste-based Kh-BC) in the present work. Subsequent to the BC production from specified wastes, chemical structure, thermal properties, scanning electron microscope (SEM) analysis, water uptake, and antibacterial activity of BC were analyzed. Among all wastes studied, mixed-vegetable peel and pea pod were positive influencers on BC synthesis and Fourier-transform infrared (FT-IR) spectra of BC membranes produced from wastes were very similar to that obtained from mannitol as a control. Additionally, waste-based Kh-BC has higher biodegradability and thermal stability than the Kh-BC produced from the control medium. Although it has a fragile structure, its water holding capacity and porous structure appear similar to standard BC. Moreover, waste-based Kh-BC could be impregnated with antibiotics to obtain the antibacterial BC membrane. Therefore, the present work showed that vegetable wastes could be valorized for BC production and waste-based Kh-BC is a promising biopolymer candidate for medical and pharmaceutical applications according to its properties.
Keywords: Bacterial cellulose; Food waste; Pea pod; Celery root peel; Mixed vegetable peel; Valorization; BACTERIAL CELLULOSE PRODUCTION; DRUG-DELIVERY SYSTEMS; LOW-COST SUBSTRATE; WASTE; RESIDUES; STRAIN; MEDIA